Three-dimensional rotating viscous flow past a permeable stretching/shrinking sheet with convective boundary condition - Hafidzuddin, M. E. H.; Arifin, N. M.; Nazar, R. M.; Pop, I. (Mathematical Modeling and Computing, 2023)
The study of three-dimensional rotating boundary layer flow approaching a stretching or shrinking surface under convective boundary conditions is presented in this paper. This study expands the scope of previous researchers' work to encompass broader scenarios, including situations involving mass transfer (suction) on the wall, the Biot number and cases featuring a shrinking surface. It is found that the increase of suction and rotating parameters leads to a noticeable rise in both the local skin friction coefficients and the local Nusselt number, and the solutions to the governing ordinary differential equations exhibit a dual-branch nature, comprising both upper and lower branch solutions, within a specific range of the governing parameters.